(3eQTO GdCfGe Edi OGQ GdSdGe aj TQYI GdESdGes - (3bhQO OOg CafOj, eMeO Hf YeQ bhQO CafOj, J(B996(3g`s
(3ChdgG (B:s
(3aUd aj aVGFd HYV GdCWYeI hGdahGcg hGdCTQHI haj GdMOjK CfHQjd Ydjg GdSdGe CeQ fHjfG Udi Gddg Ydjg hSde Cf jCcd GdgQjSI djTJO HgG XgQg djROGO (B((3cPG(B) (3bhJg dbjGe Gddjd aCcds
(3BNQgG (B:s
(3hYf YGFTI QVj Gddg YfgG bGdJ(B: (3SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd(B: (3dG JSHhG CehGJce adG jMd SHge hMQGe Ydjce Pdc aGJbhG Gddg hchfhG Ydi MPQ cPG aj NGdUI GdMbGFbs
(3efbhdI Yf fSNI GdeDda , HgG WjGQGJ aj YOI ehGVYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 3 / 564s
(3cTa GdXfhf(B: 2 / 1044s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs